PeerJ Physical Chemistry 2019
DOI: 10.7717/peerj-pchem.6
|View full text |Cite
|
Sign up to set email alerts
|

Spectrometric and computational studies of the binding of HIV-1 integrase inhibitors to viral DNA extremities

Abstract: Three integrase strand transfer inhibitors are in intensive clinical use, raltegravir (RAL), elvitegravir (EVG) and dolutegravir (DTG). The onset of integrase resistance mutations limits their therapeutic efficiency. As put forth earlier, the drug affinity for the intasome could be improved by targeting preferentially the retroviral nucleobases, which are little, if at all, mutation-prone. We report experimental results of anisotropy fluorescence titrations of viral DNA by these three drugs. These show the DTG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 75 publications
1
3
0
Order By: Relevance
“…E tot (SIBFA) displayed trends consistent with E (QC). This study, along with our previous ones (El Hage et al, 2014El Khoury et al, 2019) shows that it is possible to design, in a piece-wise fashion, novel derivatives targeting a well-defined, highly conserved, subset of the recognition site of a large macromolecular target. It also constitutes an essential validation step prior to large-scale polarizable molecular dynamics simulations of the complex of the entirety of the drug with the entirety of the target.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…E tot (SIBFA) displayed trends consistent with E (QC). This study, along with our previous ones (El Hage et al, 2014El Khoury et al, 2019) shows that it is possible to design, in a piece-wise fashion, novel derivatives targeting a well-defined, highly conserved, subset of the recognition site of a large macromolecular target. It also constitutes an essential validation step prior to large-scale polarizable molecular dynamics simulations of the complex of the entirety of the drug with the entirety of the target.…”
Section: Discussionsupporting
confidence: 53%
“…Could, thus, increases of the INSTI-INT binding affinities be attempted upon focusing on the sole "ternary" complexes of G 4 , C 16 , and a halobenzene ring? Second, recent spectrometric and computational studies of the binding of INSTIs to viral DNA extremities showed the ranking of affinities to be governed by the enthalpy ( H) component of the binding free energies ( G), the entropy component (T S) being similar for all three complexes (El Khoury et al, 2019), a "signature" for intercalative binding (Chaires, 2006). Furthermore, the H ranking of the three inhibitor affinities was itself paralleled by the corresponding ranking of the ab initio quantum chemistry (QC) intermolecular interaction energies, E(QC), of their halobenzene rings with the sole G 4 /C 16 base pair.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted by Khoury et al ( 2019 ) showed that EVG binding to intasome has a slight preference over DTG and RAL, indicating that additional interactions of the diketo acid groups of the drugs with DNA could be essential to further enable preferential binding of DTG. EVG affects not only the residues in direct contact but also the outer-shell residues indirectly bound, particularly the double mutations, like Q148R/H and G140S/A, which has a synergetic effect on its efficacy.…”
Section: Computational Studiesmentioning
confidence: 99%
“…The X-ray structural analysis demonstrated that in the IN–vcDNA complex, the halobenzyl ring stacks over C16 (upstream), while the C–X bond points towards the centre of the G4 (downstream) of the second strand. Therefore, a surge in the drug–vcDNA complex stability draws a parallel with an increase in drug activity and a decline in viral resistance, indicating the vitality of vcDNA end recognition for the binding affinity of INSTIs to the intasome (Khoury et al 2019 ).…”
Section: Computational Studiesmentioning
confidence: 99%